Treating rare tumors with the assistance of the expert virtual consultation system: two cases of juvenile granulosa cell tumors. Issue 6 (December 2021) - Hovsepyan, Shushan; Hakobyan, Lusine; Mkhitaryan, Armen; Terenziani, Monica; Ferrari, Andrea; Sironi, Giovanna; Schneider, Dominik T.; Tamamyan, Gevorg
Background: The lack of internationally recognized guidelines for very rare tumors, such as juvenile granulosa cell tumors (JGCTs), which are nonepithelial, unusual ovarian tumors, is a challenge for pediatric oncologists, especially in developing countries with limited resources and experience in treating rare tumors. Methods: We report clinical data of 2 girls with JGCTs treated at the Pediatric Cancer and Blood Disorders Center of Armenia with the assistance of the EXPeRT (European Cooperative Study Group for Pediatric Rare Tumors) international cooperation panel. Case presentation: Two girls (16 and 15 years old) with JGCTs of the ovaries, stage Ic, underwent surgery and, with consultation through an online advisory board (http://vrt.cineca.it/ ), received 4 cycles of chemotherapy according to the PEI regimen (cisplatin, etoposide, ifosfamide). Conclusion: Very rare tumors, especially in advanced stages, have limited data and a low survival rate. International collaboration with the EXPeRT group is beneficial for physicians with limited experience and facilitates research in pediatric oncology.